Psychotic like experiences in healthy adolescents are underpinned by lower fronto-temporal cortical gyrification: a study from the IMAGEN consortium - Maitra, Raka; Horne, Charlotte M; O’Daly, Owen; Papanastasiou, Evangelos; Gaser, Christian; Banaschewski, Tobias; Flor, Herta; Nees, Frauke; Hohmann, Sarah; Millenet, Sabina (Schizophrenia bulletin, 2023)
Psychotic Like Experiences (PLEs) are widely prevalent in children and adolescents and increase the risk of developing psychosis. Cortical gyrification characterizes brain development from in utero till about the first 2 years of life and can be measured in later years as static gyrification changes demonstrating neurodevelopment and dynamic gyrification changes reflecting brain maturation during adolescence. We hypothesized that PLEs would be associated with static cortical gyrification changes reflecting a neurodevelopmental abnormality.We studied 1252 adolescents recruited in the IMAGEN consortium. We used a longitudinal study design, with Magnetic Resonance Imaging measurements at age 14 years and age 19 years; measurement of PLEs using the Community Assessment of Psychic Experiences (CAPE) questionnaire at age 19 years; and clinical diagnoses at age 23 years.Our results show static gyrification changes in adolescents with elevated PLEs on 3 items of the CAPE—voice hearing, unusual experiences of receiving messages, and persecutory ideas—with lower cortical gyrification in fronto-temporal regions in the left hemisphere. This group also demonstrated dynamic gyrification changes with higher cortical gyrification in right parietal cortex in late adolescence; a finding that we replicated in an independent sample of patients with first-episode psychosis. Adolescents with high PLEs were also 5.6 times more likely to transition to psychosis in adulthood by age 23 years.This is the largest study in adolescents that demonstrates fronto-temporal abnormality of cortical gyrification as a potential biomarker for vulnerability to PLEs and transition to psychosis.
Vorab online veröffentlicht: 05. Oktober 2022
Gesehen am 08.07.2024